Malnutrition and its Association with Heart Failure Severity in Children with Congenital Heart Disease: A Cross- Sectional Study in Indonesia - Ferdy Lainsamputty; Fransiskus Xaverius Widiantoro; Sumarmi Sumarmi; Keysha Maryel Pandelaki; Joy RJ Maramis (PT.Mantaya Idea Batara, 2026)
Background: Congenital heart disease (CHD) is a major cause of pediatric morbidity and mortality. Malnutrition often coexists with CHD and may be associated with poorer heart failure (HF) outcomes. The study aimed to assess the prevalence of malnutrition (underweight, wasting, and stunting) and its association with HF severity in children with CHD. Methods: This was a single-center cross-sectional study at a tertiary hospital in Indonesia. The study included 41 pediatric CHD patients, recruited using a total sampling technique. Anthropometric data were assessed based on World Health Organization standards. HF severity was evaluated using the Modified Ross Score. The Mann-Whitney, Kruskal- Wallis, Spearman correlation, and multiple linear regression were applied. Result: Among participants, 26.8% were underweight, 22.0% were wasted, and 36.6% were stunted. The mean HF severity score was 3.07 (SD = 1.40). Most were categorized as having mild HF (63.4%). Residence (Z = 1.967; p = 0.049), underweight (Z = -2.394; p = 0.017), stunting (Z = -2.497; p = 0.013), and wasting (Z = -2.236; p = 0.025) were significantly associated with higher HF severity scores. WAZ score significantly correlated with HF severity (r = -0.348; p = 0.026). Stunting (β = -0.334; 95% CI: -1.787 to -0.138; p = 0.023) and wasting (β = -0.316; 95% CI: -2.018 to -0.098; p = 0.032) were significant determinants of HF severity. Conclusion: Stunting and wasting were independently associated with greater HF severity. These findings suggest the potential clinical importance of early nutritional screening and multidisciplinary interventions to mitigate HF progression. Given the single-center design and small sample size, further multicenter studies are needed to confirm these findings and strengthen causal inference.